FINANCIAL MANAGEMENT ANALYSIS IN NON-PROFIT ORGANIZATIONS OF MUHAMMADIYAH MERTOYUDAN ORPHANAGE IN MAGELANG REGENCY - Budi Novianingsih; Risma Wira Bharata (Transpublika Publisher, 2023)
This study aims to determine the process of obtaining funds, management of funds management, implementation of bookkeeping and obstacles encountered related to the implementation that occurred at the Muhammadiyah Mertoyudan Orphanage in Magelang Regency. Methods of data analysis used was qualitative methods. In this study, data were obtained through primary data, namely data sources obtained directly from the original source (not through intermediary media). The data in this study were carried out using the observation method at the Muhammadiyah Mertoyudan Orphanage in Magelang district. From the results of this study, it can be concluded that financial management at the Muhammadiyah Mertoyudan Orphanage in Magelang district is carried out with the staff managing the Budget Execution Document allocating funds that have been provided for the needs of the orphanage for 1 year. In carrying out the financial accounting of the institution, the Muhammadiyah Mertoyudan Orphanage in Magelang uses PSAK 45 concerning non-profit foundations.